2019
DOI: 10.1186/s12882-019-1621-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment of curcumin improves hepatic lipid metabolism and alleviates the renal damage in adenine-induced chronic kidney disease in Sprague-Dawley rats

Abstract: BackgroundChronic kidney disease (CKD), including nephrotic syndrome, is a major cause of cardiovascular morbidity and mortality. The literature indicates that CKD is associated with profound lipid disorders due to the dysregulation of lipoprotein metabolism which progresses kidney disease. The objective of this study is to evaluate the protective effects of curcumin on dyslipidaemia associated with adenine-induced chronic kidney disease in rats.MethodsMale SD rats (n = 29) were divided into 5 groups for 24 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 100 publications
3
36
0
Order By: Relevance
“…The effects of CURC on renal damage have been investigated in animal models, both in vivo and in vitro. Chronic supplementation of CURC has been shown to protect renal damage in various chemically-induced nephrotoxicity and renal injury models [57]. Our morphologic results support the hypothesis that CURC, as other antioxidants [27], reduces glomerular and tubular damage, kidney inflammation and tubulointerstitial fibrosis in rats, potentially preserving kidney function.…”
Section: Discussionsupporting
confidence: 82%
“…The effects of CURC on renal damage have been investigated in animal models, both in vivo and in vitro. Chronic supplementation of CURC has been shown to protect renal damage in various chemically-induced nephrotoxicity and renal injury models [57]. Our morphologic results support the hypothesis that CURC, as other antioxidants [27], reduces glomerular and tubular damage, kidney inflammation and tubulointerstitial fibrosis in rats, potentially preserving kidney function.…”
Section: Discussionsupporting
confidence: 82%
“…In this study, no significant changes were observed in HDL levels in the cNE-MCFA group. In a report published by Ghelani et al (2019) [ 51 ], SD rats with adenine-supplemented diets and three different curcumin concentrations (50, 100, and 150 mg) for 24 days were evaluated; the data revealed that only the 100 and 150 mg/kg doses increased HDL levels, attributing the effect to the concentration of curcumin; however, the NE-MCFA group showed a slight increase in HDL levels. Zhang et al (2016) [ 52 ] determined that the use of MCT increased HDL and decreased serum bile acid levels when compared to long chain triacylglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…The first discovered pharmacological activity of curcumin is an antibacterial effect, found in 1949 [ 29 ]. Further studies focused on revealing other therapeutic and biological activities of curcumin including antiproliferative [ 30 ], antimetastatic [ 31 ], antioxidant [ 32 ], anti-inflammatory [ 33 ], antidiabetic [ 34 ], antiangiogenic [ 35 ], immunomodulatory [ 36 ], antitumor [ 37 ], antiatherosclerotic [ 38 ] and a lipid lowering effect [ 39 ] and regulating blood pressure [ 40 ].…”
Section: Curcumin: Structure and Pharmacokineticsmentioning
confidence: 99%